Mechanical Work Occupational Safety Risk Analysis Using JSA and HIRARC at PT ABB - Fannisha Aura Rifqo; Bintang Nidia Kusuma; Muhammad Ali Akbar (Fakultas Teknik Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to identify potential hazards, assess occupational safety risks, and develop safety improvement recommendations for mechanical work at PT Arasindo Bina Bersama using the Job Safety Analysis (JSA) and Hazard Identification, Risk Assessment, and Risk Control (HIRARC) methods. This study employed qualitative and quantitative approaches through field observations, interviews, and documentation. JSA was used to identify potential hazards at each stage of the work process, while HIRARC was applied to assess risk levels and determine appropriate control measures based on the hierarchy of controls. The results identified three critical mechanical activities, namely hydraulic hose and pipe installation, axle component dismantling and installation, and hydraulic pipe and hose assembly, with a total of 26 identified hazards. The HIRARC risk assessment classified the hazards into 1 Very High Risk, 4 High Risk, 18 Medium Risk, and 3 Low Risk categories. Hazards classified as Very High Risk and High Risk were prioritized for immediate implementation of control measures. Meanwhile, Medium Risk hazards required additional controls to reduce the level of risk, whereas Low Risk hazards only required periodic monitoring. Safety improvement recommendations were developed based on the hierarchy of controls, including elimination, substitution, engineering controls, administrative controls, and personal protective equipment. This study demonstrates that the integration of JSA and HIRARC provides a systematic approach to hazard identification, risk prioritization, and the development of effective control strategies to improve occupational safety and promote a sustainable occupational health and safety culture.